Organic Diet as Silent Pretreatment Strategy to Boost Immune System Against SARS-CoV-2. - Saqaina Anwar 1, Bushra Sharf 2, Muhammad Usman 1, Digvijay Panday 3, Muhammad Asif 1* (AlQalam Journal of Medical and Applied Sciences, 2020)
Nowadays, world is facing the life-threatening disease SARS-CoV-2 which creates panic situation among people because of no effective treatment modality and lack of chances to get novel vaccination. In such circumstances, self-isolation and prevention to get expose to viral environment is best strategy to safe our society. Healthy and nutritional dietary measures can facilitate us to boost our immunity system against viral attacks. In this review, we discussed the importance of organic diets that can be used to fight against SARS-CoV-2 infection by improving the immune system as pretreatment strategy. We also discussed other factors that can improve immune system such as reducing the stress and inflammation, avoid smoking and toxins and doing moderate exercise daily. Meanwhile, plasma therapy is also under examination to save patient’s life, and discussed in this review.